Pengaruh Kualitas Produk Dan Reputasi Merek Terhadap Keputusan Pembelian Dengan Harga Sebagai Variabel Intervening Pada Miss Glam Make Up Cabang Gunung Pangilun Kota Padang - Arrijalul Fikry; Yulasmi; Mardhatila Fitri Sopali (Jurnal Ekonomi dan Bisnis Digital, 2025)
This research aims to determine and try to analyze the influence of product quality and brand reputation on purchasing decisions with price as an intervening variable at Miss Glam Make Up, Gunung Pangilun Branch, Padang City. This research is a Structural Equation Modeling (SEM) model with the SmartPLS 3.0 analysis tool. The population and sample of this research is Miss Glam Make Up, Gunung Pangilun Branch, Padang City. The research results found that there was a positive and significant influence between product quality and price. There is a positive and significant influence between Brand Reputation on Price. There is a positive and significant influence between Product Quality on Purchasing Decisions. There is a positive and insignificant influence between Brand Reputation on Purchasing Decisions. There is a positive and significant influence between price on purchasing decisions. Price is able to mediate product quality on purchasing decisions. Price is able to mediate Brand Reputation on Purchasing Decisions.